The Acute VertEbRal AugmentaTion (AVERT) study: protocol for a randomised controlled, feasibility trial of spinal medial branch nerve block in hospitalised older patients with vertebral fragility fractures. Issue 6 (13th June 2022) - Tan, Chia Wei; Cameron, Maribel; Arlachov, Yuriy; Bastounis, Anastasios; Bishop, Simon; Czernicki, Michal; Drummond, Avril; Fakis, Apostolos; Pasku, Dritan; Sahota, Opinder
Abstract : Introduction: Vertebral fragility fractures (VFFs) are the most common type of osteoporotic fracture found in older people, resulting in increasing morbidity and excess mortality. These fractures can cause significant pain, requiring admission to hospital. Vertebroplasty (VP) is effective in reducing pain and allowing early mobilisation in hospitalised patients. However, it may be associated with complications such as cement leakage, infection, bleeding at the injection site and fracture of adjacent vertebrae. It is also costly and not readily accessible in many UK hospitals. A recent retrospective study reported that spinal medial branch nerve block (MBNB), typically used to treat facet arthropathy, had similar efficacy in terms of pain relief compared with VP for the treatment of painful VFF. However, to date, no study has prospectively compared MBNB to VP. We therefore propose a prospective feasibility randomised controlled trial (RCT) to compare the role of MBNB to VP, in hospitalised older patients. Method: A parallel, two-arm RCT with participants allocated on a 1:1 ratio to either standard care-VP or MBNB in hospitalised patients aged over 70 with acute osteoporotic vertebral fractures. Follow-up will be at weeks 1, 4 and 8 post intervention. The primary objective is to determine the feasibility and design of a future trial, including specific outcomes of recruitment, adherence to randomisation and safety. Embedded within the trial will be a health economic evaluation to understand resource utilisation and implications of the intervention and a qualitative study of the experiences and insights of trial participants and clinicians. Secondary outcomes will include pain scores, analgesia requirements, resource use and quality of life data. Ethics and dissemination: Ethical approval was granted by the Yorkshire & the Humber Research Ethics Committee ( reference 21/YH/0065 ). AVERT (Acute VertEbRal AugmentaTion) has received approval by the Health Research Authority ( reference IRAS 293210 ) and is sponsored by Nottingham University Hospitals NHS Trust ( reference 21HC001 ). Recruitment is ongoing. Results will be presented at relevant conferences and submitted to appropriate journals for publication on completion. Trial registration number: ISRCTN18334053 .